2003
DOI: 10.1167/iovs.01-0131
|View full text |Cite
|
Sign up to set email alerts
|

Development of Refractive Error and Strabismus in Children with Down Syndrome

Abstract: The retention or development of infantile refractive errors in many children with Down syndrome indicates a failure of emmetropization. All children were at risk of strabismus whatever the refractive error. The findings have implications for timing of screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 33 publications
5
96
2
3
Order By: Relevance
“…This increase in the prevalence of refractive errors in children with Down syndrome might reflect a failure of emmetropization. 12 Earlier reports have documented that esotropia is common and exotropia is uncommon in individuals with …”
Section: Discussionmentioning
confidence: 99%
“…This increase in the prevalence of refractive errors in children with Down syndrome might reflect a failure of emmetropization. 12 Earlier reports have documented that esotropia is common and exotropia is uncommon in individuals with …”
Section: Discussionmentioning
confidence: 99%
“…65,66 A more dramatic failure of emmetropisation can be observed in Down's syndrome despite the good visual acuity usually observed in this condition. 67,68 It has been proposed that the apparent absence of emmetropisation in Down's syndrome would reveal the underlying pattern of genetically determined eye growth. 69 The patterns of refractive development in Down's syndrome are instead highly variable and display the mathematical features of a random walk typical of a stochastic process.…”
Section: Clinical Examples Of a Failure Of Emmetropisationmentioning
confidence: 99%
“…69 The patterns of refractive development in Down's syndrome are instead highly variable and display the mathematical features of a random walk typical of a stochastic process. 67,68 A comprehensive model of the mechanisms involved in refractive development This paper has reviewed the major influences on refractive development from birth to adulthood. These are the initial refraction at birth, the efficacy and duration of the emmetropisation process in the first few years of life, the poorly understood mechanisms of myopia onset and progression, stochastic influences on eye growth, and, more rarely, sources of major genetic bias towards myopia or hyperopia.…”
Section: Clinical Examples Of a Failure Of Emmetropisationmentioning
confidence: 99%
“…These findings suggest that reported prevalence estimates vary by the definition used for refractive errors and the techniques used to identify refractive errors. More recently, Cregg et al [2003] found that refractive errors among infants with Down syndrome increased with age from infancy to 30 months, a pattern opposite of that expected in early child development.…”
Section: Vision Problems Among Specific Populationsmentioning
confidence: 82%
“…(Table 1) [Maino et al, 1990;Pueschel, 1995;Saenz, 1999;Smith, 2001]. The prevalence of strabismus has been reported to range from 9 to 69% among individuals with Down syndrome, compared with Ͻ1 to 10% in the general population and 4 to 45% in the overall population of individuals with ID [Cullen and Butler, 1963;Lyle et al, 1972;Markovits, 1975;Jaeger, 1980;Woodruff et al, 1980;NCHS, 1983;Levy, 1984;Shapiro and France, 1985;Jacobson, 1988;Caputo et al, 1989;Aitchison et al, 1990;Catalano, 1990;Cooley and Graham, 1991;Hestnes et al, 1991;Sacks et al, 1991;Pérez-Carpinell et al, 1994;Prasher, 1994;Roizen et al, 1994;Berk et al, 1996;da Cunha and Moreira, 1996;Maino et al, 1996;McCulloch et al, 1996;Block et al, 1997;Woodhouse et al, 1997van Allen et al, 1999;Buch et al, 2001;Merrick and Koslowe, 2001;Cregg et al, 2003;van Splunder et al, 2003bvan Splunder et al, , 2004Gormezano and Kaminski, 2005;Murphy et al, 2005]. In addition, the prevalence of cataracts, which tends to increase with age in the general population, increases to a greater extent with age for individuals with Down syndrome …”
Section: Vision Problems Among Specific Populationsmentioning
confidence: 99%